Integrated Digital Marketing Communication Strategy of Primago Islamic Boarding School in Building Netizen Cognitive - ARDHOYO, Novalia Agung Wardjito; SUNARTO, Sunarto; ALIFAHMI, Hifni (International Journal of Environmental, Sustainability, and Social Science, 2023)
Digital transformation develops and disrupts the business sector and the economy. All Primago marketing communication activities are mediated digitally. The basic problem of this research is that Primago Digital's marketing communication activities need a model. This model is expected to deliver that effectiveness and efficiency in each Primago digital marketing communication program. The aims of this research are (1) to find the factors to be considered in designing an integrated digital marketing communication strategy for Primago. (2) To find priority choices in building netizen cognition. It is based on the multiple assessment criteria of experts. This study uses the theory of Computer-Mediated Communication, Information Integration Theory, and then the concept of Integrated Marketing Communications. For methodology, this study uses a post-positivism paradigm. The results of the interviews and dissemination of disclosures were then analyzed without the in-depth involvement of the researcher. Qualitative and quantitative methods are used simultaneously in this study. Based on the analysis of this study resulted in conclusions. (1) factors must be considered in designing Primago's digital marketing communication strategy. Among others are Accessible, Affordable, Connectivity, Costumize, and Real-Time Measurement. (2) The priority for choosing the right digital integrated marketing communication strategy for Primago in building netizen cognition sequentially is managing the website. Then simultaneously managing Facebook and Instagram, the third is YouTube and TikTok.